Mother-Tongue in Modern Japanese Literature and Criticism Toward a New Polylingual Poetics - Yokota-Murakami, Takayuki (Springer Nature Singapore : Imprint: Palgrave Macmillan, 2018)
XV, 183 p. 2 illus.